Successful emotion regulation via cognitive reappraisal in authentic pride: Behavioral and event-related potential evidence - Lin, Daichun; Bi, Jianru; Zhang, Xiaoxuan; Zhu, Feng; Wang, Yanmei (Frontiers in Human Neuroscience, 2022)
The present study explored whether authentic pride (AP) and hubristic pride (HP) were differently associated with cognitive reappraisal strategy. In study 1, undergraduates (n = 235) completed a battery of self-report questionnaires, including the Authentic and Hubristic Pride-Proneness Scale (AHPPS), Emotion Regulation Questionnaire (ERQ), and emotion regulation questionnaire (ERP-R). The results showed that AP significantly predicted successful down-regulation of negative emotions via a spontaneous cognitive reappraisal strategy. However, hubristic pride (HP) was negatively associated with spontaneous cognitive reappraisal. In study 2, participants with trait AP (n = 31) and trait HP (n = 29) undergoing continuous electroencephalogram (EEG) recording were required to reinterpret emotional pictures to down-regulate/up-regulate their negative/positive emotional reactions. The results showed that individuals with AP reported lower levels of emotional arousal and lower amplitudes of late positive potentials (LPPs) than did individuals with HP in response to negative pictures during the down-regulation of negative emotions, but not during passive viewing or up-regulation of positive emotions. Across two studies, these findings showed that individuals with AP could utilize the cognitive reappraisal strategy (spontaneously in daily life and under experimental instructions) to down-regulate negative emotions more successfully relative to individuals with HP.